Students’ perspective on simulation-based learning for undergraduate paediatrics module - Farin Masra,; Hong, Joyce Soo Synn; Lau, Doris Sie Chong (Penerbit Universiti Kebangsaan Malaysia, 2021)
The emergence of COVID-19 has greatly disrupted most areas of student lives and medical students are perhaps among those who have been greatly affected, especially in their clinical training. Due to restrictions, bedside teachings and interactions between students and patients were limited, consequently reducing their clinical experience. Thus, simulation-based learning has been incorporated into the Year 4 undergraduate paediatric rotation using various methods such as paediatric mannequin simulators and simulated patients as well as online simulated case discussions. A total of 91 Year 4 undergraduate medical students who participated in this simulation-based teaching and learning method answered a quick survey at the end of their semester to evaluate their acceptance on these newly introduced methods. The students accepted online simulation-based case discussion and role-play using simulated patients as effective teaching and learning methods. However, they ultimately expressed that direct encounter with patients remained the best modality to learn examination skills in paediatric posting. Although simulation-based learning cannot fully replace bedside teaching, it can be incorporated into the undergraduate medical curriculum to complement each other, especially in unprecedented times like this.